2019
DOI: 10.3390/su11010262
|View full text |Cite
|
Sign up to set email alerts
|

Information Disclosure Ranking, Industry Production Market Competition, and Mispricing: An Empirical Analysis

Abstract: Improving the transparency of corporate information disclosure is a key principle of corporate governance in Taiwan. This study uses the information disclosure assessment system established by the information disclosure and transparency ranking system to explore whether information transparency can reduce the degree of mispricing. The study uses the data of 10,686 listed companies in Taiwan for the period from 2005 to 2014. We find that a higher information disclosure ranking (IDR) of rated companies correspon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…The HHI was utilised as the market competition scale in this study, and it is one of the most commonly used variables to quantify competition. The HHI Concentration Index is used to assess the market competitiveness variable, which influences industry concentration, entry barriers, and risks to firms and managers (Wang et al, 2019), as well as threats to firms and managers (Tian & Twite, 2011). A higher HHI indicates a less competitive or stable environment.…”
Section: Measuring Market Competitionmentioning
confidence: 99%
“…The HHI was utilised as the market competition scale in this study, and it is one of the most commonly used variables to quantify competition. The HHI Concentration Index is used to assess the market competitiveness variable, which influences industry concentration, entry barriers, and risks to firms and managers (Wang et al, 2019), as well as threats to firms and managers (Tian & Twite, 2011). A higher HHI indicates a less competitive or stable environment.…”
Section: Measuring Market Competitionmentioning
confidence: 99%
“…However, numerous other studies argue that information disclosure can reduce financing costs. Higher information disclosure quality can improve market performance and boost a firm's financial indicators (Chu et al, 2019;Wang et al, 2019). In addition to being significantly and positively correlated with company performance (Jiao, 2011), information disclosure reduces leverage risk (Pan et al, 2015), market value deviation (Zhu et al, 2020), and stock price delay risk (Gong et al, 2019) and increases accounting conservatism (Shen et al, 2021) and stock liquidity (Schoenfeld, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The research was based on information disclosure and transparency which is a narrower aspect of corporate governance and the results showed that the concentration of ownership could be harmful to the minority shareholders as it decreases the information transparency and disclosure (Yasser, Mamun, & Ahmed 2016). In short, the company which is owned and managed at the same time by a single individual can reduce the level of information transparency and hence reduces the market capitalization (Wang et al 2019). The studies suggest that the Securities and Exchange Commission of Pakistan (SECP) should encourage the firms to disclose more information than just the mandatory requirements in order to make the current investors feel more protected and attract the potential investors.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%